Cultivation of cardamom (Elettaria cardamomum Maton) in homesteads - HOSMANI, V S KORIKANTHIMATH, G M HIREMATH, M M (Journal of Spices and Aromatic Crops, 1998)
Trials on cultivation of cardamom (Elettaria cardamomum) in homesteads conducted during 1991-93 in an area of 0.05 ha under controlled shade at Chettalli (Karnataka, India) resulted in a yield of 103 kg of dry cardamom within 30 months and an actual gross return of Rs. 47,388, net return of Rs. 26,175 and benefit-cost ratio of 2. It also generated employment of 380 labour days for effective utilisation of spare time besides productive utilisation of backyards for profitable cultivation of cardamom.